Related-Key Cryptanalysis on the Full PRINTcipher Suitable for IC-Printing - Yuseop Lee; Kitae Jeong; Changhoon Lee; Jaechul Sung; Seokhie Hong (International Journal of Distributed Sensor Networks)
PRINTcipher-48/96 are 48/96-bit block ciphers proposed in CHES 2010 which support the 80/160-bit secret keys, respectively. In this paper, we propose related-key cryptanalysis of PRINTcipher. To recover the 80-bit secret key of PRINTcipher-48, our attack requires 2 47 related-key chosen plaintexts with a computational complexity of 2 60 · 62 . In the case of PRINTcipher-96, we require 2 95 related-key chosen plaintexts with a computational complexity of 2 107 . These results are the first known related-key cryptanalytic results on them.